Sex-based differences in obstructive sleep apnea and atrial fibrillation: Implication of atrial fibrillation burden - Chou-Han Lin; Yen-Bin Liu; Lian-Yu Lin; Hui-Chun Huang; Li-Ting Ho; Yen-Wen Wu; Ling-Ping Lai; Wen-Jone Chen; Yi-Lwun Ho; Chih-Chieh Yu (International Journal of Cardiology: Heart & Vasculature, 2024)
Background: Obstructive sleep apnea (OSA) is a risk factor for atrial fibrillation (AF); however, it is unclear whether AF increases the risk of OSA. Furthermore, sex differences among patients with both AF and OSA remain unclear. We aimed to determine the association between an increased AF burden and OSA and investigate the differences in clinical characteristics between women and men with AF and OSA. Methods: This was a descriptive, cross-sectional analysis from a prospective cohort study. Patients with non-valvular AF were recruited from the cardiac electrophysiology clinic of a tertiary center; they underwent a home sleep apnea test and 14-day ambulatory electrocardiography. Moderate-to-severe OSA was defined as an apnea-hypopnea index of ≥15. Results: Of 320 patients with AF, 53.4% had moderate-to-severe OSA, and the mean body mass index (BMI) was 25.6 kg/m2. Less women (38.2%) had moderate-to-severe OSA than men (59.3%) (p < 0.001). In the multivariate analysis, age, being a man, and BMI were significantly associated with moderate-to-severe OSA. AF burden was associated with moderate-to-severe OSA only in men (odds ratio: 1.008; 95% confidence interval: 1.001–1.014). Women and men with OSA had similar BMI (p = 0.526) and OSA severity (p = 0.754), but women were older than men (70.1 ± 1.3 vs. 63.1 ± 0.9 years, p < 0.001). Women with moderate-to-severe OSA had a lower AF burden than men did (27.6 ± 7.1 vs. 49.5 ± 3.9%, p = 0.009). Conclusions: AF burden is a sex-specific risk factor for OSA and is limited to men. In contrast, women with both AF and OSA have a lower AF burden than men, despite being older and having similar OSA severity and body habitus. Thus, AF may develop later in women with OSA than in men.